Development of Clinical and Morphometric Classification of Macular Edema in Retinal Vein Occlusions - A. A. Fil; E. L. Sorokin; O. V. Kolenko (Oftalʹmologiâ, 2022)
Purpose. To study the morphometric features of macular edema in occlusions of the retinal veins, to determine and systematize the conditional gradations of the degrees of its severity.Patients and methods. 67 patients (67 eyes) were recruited using a continuous sampling method. Their age ranged from 38 to 84 years (on average 60.0 ± 10.5 years). Among them there were 27 men and 41 women. In 19 patients, there was an occlusion of the central retinal vein (28 %), in 48 people — occlusion of its branches (72 %). The lesions of the superior temporal branch prevailed — 32 people (65 %), 16 patients had occlusion of the inferior temporal branch (35 %). Systematization of the obtained data was carried out with the allocation of morphometric gradations of the severity of macular edema against the background of retinal vein occlusions.Results. According to our data, the morphometric parameters of the macular retina in the presence of macular edema were characterized by a wide range of gradations in the thickness of the foveal retina and the volume of the macular retina (from 239 to 861 μm and from 10,4 to 17,4 mm3 respectively).The morphological features of macular edema in retinal vein occlusions are the formation of cystic cavities in the outer and inner layers of the retina, convex deformation of the retinal profile, and the development of neuroepithelial detachment in 21 % of cases. Taking into account the data obtained, we proposed a conditional morphometric classification of the severity of macular edema in retinal vein occlusions. A mild degree of macular edema was characterized by values of the foveal retinal thickness index up to 400 μm; for medium — from 401 to 600 microns; for severe macular edema — over 600 microns. In accordance with our own conditional clinical morphometric classification of the severity of macular edema, mild macular edema was determined in 32 %, medium degree — in 43 %, severe — in 25 % of patients’ eyes.Conclusion. The identification of various clinical and morphometric degrees of severity of macular edema, in our opinion, is of practical importance, since it will allow more optimal and objective selection of the most optimal treatment tactics, taking into account the individual morphometric characteristics of the patient’s macular region.